Dicksonia timorense (Diksoniaceae), a hemi-epiphytic new species of tree fern endemic on Timor Island, Indonesia - Adjie, Bayu; Kurniawan, Agung; Sahashi, Norio; Watano, Yasuyuki (REINWARDTIA, 2012)
Dicksonia timorense B. Adjie is described and illustrated as an endemic new species from Timor Island, Indonesia. Population, hemi-epiphytic trait and phylogenetic relationship based on cpDNA sequences are discussed.